Down‐regulation of GAS5 ameliorates myocardial ischaemia/reperfusion injury via the miR‐335/ROCK1/AKT/GSK‐3β axis. Issue 12 (18th October 2019) - Wu, Nan; Zhang, Xiaowen; Bao, Yandong; Yu, Hang; Jia, Dalin; Ma, Chunyan
Abstract: Growth arrest‐specific transcript 5 (GAS5), along non‐coding RNA (LncRNA), is highly expressed in hypoxia/reoxygenation (H/R)‐cardiomyocytes and promotes H/R‐induced apoptosis. In this study, we determined whether down‐regulation of GAS5 ameliorates myocardial ischaemia/reperfusion (I/R) injury and further explored its mechanism. GAS5 expression in cardiomyocytes and rats was knockdown by transfected or injected with GAS5‐specific small interfering RNA or adeno‐associated virus delivering small hairpin RNAs, respectively. The effects of GAS5 knockdown on myocardial I/R injury were detected by CCK‐8, myocardial enzyme test, flow cytometry, TTC and terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) staining. qRT‐PCR and luciferase reporter assay were carried out to analyse the relationship between GAS5 and miR‐335. The regulation of GAS5 on Rho‐associated protein kinase 1 (ROCK1) expression, the activation of PI3K/AKT/GSK‐3β pathway and mitochondrial permeability transition pore (mPTP) opening was further evaluated. The results indicated that GAS5 knockdown enhanced the viability, decreased apoptosis and reduced the levels of lactate dehydrogenase and creatine kinase‐MB in H/R‐treatment cardiomyocytes. Meanwhile, down‐regulation of GAS5 limited myocardial infarct size and reduced apoptosis in I/R‐heart. GAS5 was found to bind to miR‐335 and displayed a reciprocal inhibition between them. Furthermore, GAS5 knockdown repressed ROCK1 expression, activated PI3K/AKT, thereby leading to inhibition of GSK‐3β and mPTP opening. These suppressions were abrogated by miR‐335 inhibitor treatment. Taken together, our results demonstrated that down‐regulation of GAS5 ameliorates myocardial I/R injury via the miR‐335/ROCK1/AKT/GSK‐3β axis. Our findings suggested that GAS5 may be a new therapeutic target for the prevention of myocardial I/R injury.